Correlation analysis of serum CHI3L1, HMGB1 and CD62E detection with the prognosis of Mycoplasma pneumoniae in children: Serum CHI3L1, HMGB1 and CD62E in Mycoplasma pneumoniae in children - Yang, Hui; Zhang, Tingli; Zhang, Xiaoqi; Yang , Xu; Jiang, Xiaoan; Chen, Bo (Journal of Medical Biochemistry, 2026)
[Objective] To evaluate the clinical value of serum Chitinase-3-like protein 1 (CHI3L1), high mobility group protein 1 (HMGB1), and CD62E detection for determining the severity and prognosis of Mycoplasma pneumoniae in children.[Methods] A total of 476 children with Mycoplasma pneumoniae who were diagnosed and treated at this hospital from January 2023 to March 2025 were selected as the Mycoplasma pneumoniae infection group. The healthy control group consisted of 120 kids who had hospital examinations over the same time period. Serum CHI3L1, HMGB1, and CD62E levels were examined between the Mycoplasma pneumoniae infection group and the healthy control group. To investigate the risk factors for a bad outcome in kids infected with Mycoplasma pneumoniae, univariate and multivariate logistic regression analyses were employed. Serum CHI3L1, HMGB1, and CD62E levels were investigated in relation to Mycoplasma pneumoniae severity and their predictive power for a poor outcome.[Results] HMGB1, CD62E, and CHI3L1 serum levels were significantly greater in the Mycoplasma pneumoniae infection group than in the healthy control group (P
Keywords: High mobility group protein 1; Mycoplasma pneumoniae; Correlation analysis; Chitinase-3-like protein 1; CD62E